Louisa Lawson and the Woman Question - Anne Holden Rønning (Coolabah, 2015)
The start of the women‘s press in Britain in 1855 by Emily Faithfull was an important step on the path to emancipation – women had now a voice in the media. Thirty-three years later Louisa Lawson, who has been called the first voice of Australian feminism, published the first number of The Dawn. This was a watershed in that it gave women a voice, marked women‘s political engagement in the public sphere, and employed women compositors, making available to a broader public issues which were politically relevant. In the first number Lawson asks, ―where is the printing-ink champion of mankind‘s better half? There has hitherto been no trumpet through which the concentrated voices of womankind could publish their grievances and their opinions.‖ This article will look at some of the content in the journal during the seventeen years of its existence, 1888- 1905.